PEMBELAJARAN BERDIFERESIASI DAN MOTIVASI HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V DI SEKOLAH DASAR - Lora Devian; Darmansyah (Cerdas Proklamator, 2023)
ABSTRACT One of the values and roles of teachers is to create learning that favors students, namely learning that liberates the thinking and potential of students. This is in line with differentiated learning. One of the educational philosophies according to Ki Hajar Dewantara is the "among" system, the teacher must be able to guide the strength of the participants to develop according to their nature. This study aims to describe differentiated learning and improve student motivation and learning outcomes in mathematics learning. This research was carried out at SD Negeri 09 Kampung Melayu, with the subject of the study being class V with 25 students. The research procedure starts from planning (compiling lesson plans, learning tools, observation sheets, and evaluation instruments), research implementation (application of differentiated learning), evaluation (tests at the end of each learning cycle), and reflection (identification of deficiencies and advantages of implementation at the end of the learning cycle). Data collection through obervation sheets in the learning process and through evaluation tests at the end of learning using test instruments. The data obtained were analyzed using descriptive quantitative analysis. The results of the study carried out in the first cycle were 52.00%, which showed that there were 13 students who scored above 75, and 12 students did not meet the completion standards. Then in cycle II with a completion gain of 88.00%, which shows that there are 22 students who meet the completion standard, and only 3 students who do not meet the minimum completion. The application of differentiated learning to mathematics subjects can increase the motivation of student learning outcomes through classifying student abilities, using material development that varies according to student abilities, and take an individual approach so that students are motivated to continuously improve mathematics learning